2022
DOI: 10.3389/fcell.2022.790365
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 Activity Is Essential for Focal Adhesion and Slit Diaphragm Integrity

Abstract: Glomerular podocytes build, with their intercellular junctions, part of the kidney filter. The podocyte cell adhesion protein, nephrin, is essential for developing and maintaining slit diaphragms as functional loss in humans results in heavy proteinuria. Nephrin expression and function are also altered in many adult-onset glomerulopathies. Nephrin signals from the slit diaphragm to the actin cytoskeleton and integrin β1 at focal adhesions by recruiting Crk family proteins, which can interact with the Rap guani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…First, SNPs located in a liver and kidney enhancer for RAPGEF1 at chr9 were genome-wide associated with MBzP, a metabolite of butylbenzyl phthalate (BBP) used as plasticizer for polyvinyl chloride (PVC). RAPGEF1 encodes a guanine nucleotide exchange factor, and mutations in genes of the same family have been found in patients with nephrotic syndrome type 7 and membranoproliferative glomerulonephritis (Maywald et al, 2022; Zhu et al, 2019). Second, a loss-gain CNV of 10.8 kb overlapping the whole gene MRGPRX1 was associated with oh-MiNP, a metabolite of DINP which is used primarily in the manufacture of PVC.…”
Section: Discussionmentioning
confidence: 99%
“…First, SNPs located in a liver and kidney enhancer for RAPGEF1 at chr9 were genome-wide associated with MBzP, a metabolite of butylbenzyl phthalate (BBP) used as plasticizer for polyvinyl chloride (PVC). RAPGEF1 encodes a guanine nucleotide exchange factor, and mutations in genes of the same family have been found in patients with nephrotic syndrome type 7 and membranoproliferative glomerulonephritis (Maywald et al, 2022; Zhu et al, 2019). Second, a loss-gain CNV of 10.8 kb overlapping the whole gene MRGPRX1 was associated with oh-MiNP, a metabolite of DINP which is used primarily in the manufacture of PVC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Rap1 signaling pathway has been shown to be associated with in ammation in recent years, and some studies have revealed that activation of Rap1 negatively regulates the production of pro-in ammatory cytokines (especially IL-6), which may be the mechanism by which macrophages are suppressed in the in ammatory response to early microscopic infections [23] . It is known that Rap1 mainly regulates intercellular adhesion responses, that Ra1p-mediated signaling affects endothelial permeability, and that activation of Rap1 increases cell-cell junctions and enhances barrier resistance [24,25] . Recent studies have also mentioned that the facial skin of acne patients suffers from impairment of the intrinsic barrier permeability of the stratum corneum and some defects in the intercellular lipid membrane, and the degree of impairment correlates with the severity of acne [26] .…”
Section: Discussionmentioning
confidence: 99%
“…According to research by Maywald et al, Rap1 controls adhesion proteins in podocytes, which has an impact on the formation and upkeep of the slit septum. Thus, abnormal changes in Rap1 expression may be an important cause of macroproteinuria [ 29 ]. Moreover, as a small GTPase, the sequence of Rap1 is highly consistent with that of Ras [ 30 ].…”
Section: Discussionmentioning
confidence: 99%